Comparative study of a primary school music program using computer-based, computer-assisted and teacher-led educational approaches on students' learning and attitudes - Wu, Dawn Chuang-Mae. (2008)
The purpose of this study was to compare the learning outcomes of primary school students who studied music theory using the Computer-Based Instructional (CBI) approach, the Computer-Assisted Instructional (CAI) approach and the Teacher-Led approach. The students' and teacher's attitude towards the use of technology in the music classroom was also investigated in this research. Three primary two classes were randomly selected in a government-aided primary school in Singapore and the researcher developed a pre-study survey questionnaire to gather information regarding students' musical backgrounds and their experience with computers and software. During the ten-lesson program, students were taught a) treble clef note names, b) bass clef note names, c) note values and d) rhythm. Students who had undergone the CBI and CAI approach made use of the Music Ace and Music Ace 2 CD-ROMs in their lessons. A pretest was administered to students on the onset of the program to determine their knowledge of music notation and note values. A posttest of the same structure was given at the end of the ten lessons to examine the effectiveness of the use of computers and accompanying software and/or teacher instruction.